Anatomy of the left atrial ridge (coumadin ridge) and possible clinical implications for cardiovascular imaging and invasive procedures. (15th December 2019) - Piątek‐Koziej, Katarzyna; Hołda, Jakub; Tyrak, Kamil; Bolechała, Filip; Strona, Marcin; Koziej, Mateusz; Lis, Maciej; Jasińska, Katarzyna A.; Hołda, Mateusz K.
Abstract: Background: The left atrial ridge is a structure located in the left atrium between the left‐sided pulmonary veins ostia and the orifice of the left atrial appendage. Since it was commonly misdiagnosed as a thrombus, the ridge is also known as the "coumadin" or "warfarin" ridge. The left atrial ridge is a potential source of arrhythmias and can be an obstacle in ablation procedures. This study aimed to provide information about the occurrence and spatial morphometric characteristics of the left atrial ridge. Methods and Results: The macroscopic morphology of the left atrial ridge was assessed in 200 autopsied human hearts. The ridge was observed in 59.5% of specimens and was absent in the remaining 40.5% of cases. The mean length of the ridge was 22.4 ± 5.1 mm. It was wider at its inferior sector when compared to its superior sector (9.1 ± 5.0 vs 7.9 ± 3.2 mm; P  = .028). The total wall thickness measured at the cross section of the ridge was significantly larger in the inferior than in superior sector (6.2 ± 3.5 vs 4.3 ± 1.8 mm; P  < .001), although the myocardial thickness was significantly larger at the superior sector (3.1 ± 1.4 vs 1.9 ± 0.9 mm in inferior sector, P  < .001). Conclusion: The left atrial ridge is a variable structure, present in 59.5% of humans. The ridge is significantly wider and thicker at its inferior sector, although the actual myocardial layer present within the ridge is thinner at this location. Knowledge about the left atrial ridge morphology is key in avoiding unnecessary interventions or complications during invasive procedures.